SSRP1/SLC3A2 Axis in Arginine Transport: A New Target for Overcoming Immune Evasion and Tumor Progression in Peripheral T‐Cell Lymphoma - Yimin Ren; Lei Fan; Ling Wang; Yanping Liu; Jie Zhang; Boya Wang; Ruize Chen; Xiao Chen; Lingyu Zhuang; Yaping Zhang; Handong Sun; Jianyong Li; et al. (Advanced Science)
Abstract Peripheral T‐cell lymphoma (PTCL) is a heterogeneous group of mature T‐cell malignancies with poor prognosis. Therefore, improved therapies are urgently required to improve patient outcomes. In this study, metabolic inhibitor drug screening reveals that quinacrine elicits excellent antitumor activity both in vitro and in vivo by downregulating intracellular arginine levels in PTCL. Single‐cell transcriptomic analyses reveal aberrant arginine metabolism in patients with PTCL, characterized by excessive solute carrier family 3 member 2 (SLC3A2) mediated arginine uptake preferentially in tumor cells. High SLC3A2 expression predicts poor outcomes in PTCL, as SLC3A2‐mediated arginine uptake promotes the malignant behaviors of tumor cells and induces tumor immune escape, thereby fueling tumor progression. Mechanistically, high arginine levels induce global metabolic changes, including enhanced oxidative phosphorylation by promoting nascent RNA synthesis. This work identifies structure‐specific recognition protein 1 (SSRP1), which upregulates SLC3A2, as a co‐transcription factor with JUNB. Quinacrine disrupts SLC3A2‐mediated arginine transport by targeting SSRP1. Combining quinacrine with histone deacetylase inhibitors is a promising therapeutic strategy for PTCL.